Innovación financiera y Rentabilidad de las Cooperativas de Ahorro y Crédito segmento 1 de la provincia de Chimborazo, periodo 2020-2022 - Achance Nono, Andrea Lizbeth (2024)
ABSTRACT: The financial innovation of credit unions in segment 1 in the province of Chimborazo is a significant research topic due to the rapid growth of investments in innovation and fee-generating investments that foster new growth opportunities in the financial sector. In this sense, credit unions have identified opportunities to engage in innovative activities alongside traditional ones to access new markets through the development of new financial products. Therefore, the present research aimed to determine how financial innovation impacts the profitability of Credit Unions in segment 1, province of Chimborazo, during the period 2020-2022.The research methodology is deductive with a quantitative and qualitative approach based on exploratory and descriptive documentary research. The study focused on the savings and credit cooperatives "Fernando Daquilema" and "Riobamba Ltda.," as they are the main ones in the province of Chimborazo in segment 1. Through observation and interview techniques, using observation forms and interview guides, information was collected from financial statements, results, cash flow, and financial indicators for the period 2020-2022 from the portal of the Superintendence of Popular and Solidarity Economy (SEPS). This information was used to apply profitability indicators.As a result of this research, financial innovations have a positive influence on the profitability of savings and credit cooperatives, particularly in terms of return on assets and return on equity expressed through ATMs and credit and debit cards.